Specters of war : Hollywood's engagement with military conflict - Bronfen, Elisabeth (New Brunswick, N.J. : Rutgers University Press, 2012)
Specters of War: Hollywood's Engagement with Military Conflict looks at the way war has been brought to the screen in various genres and at different historical moments throughout the twentieth century. Elisabeth Bronfen asserts that Hollywood has emerged as a place where national narratives are created and circulated so that audiences can engage with fantasies, ideologies, and anxieties that take hold at a given time, only to change with the political climate.
Introduction -- Unfinished business of the Civil War -- Home and its discontent -- War entertainment -- Choreography of battle -- Reporting the war -- Court-martial drama -- War's sustained haunting -- Conclusion.
Includes filmography.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: War films -- United States -- History and criticism; Films de guerre -- États-Unis -- Histoire et critique; PERFORMING ARTS -- Film & Video -- History & Criticism; War films; United States; Criticism, interpretation, etc